High-temperature-resistant ultrahigh-magnetic-conductivity wave-absorbing material and preparation method thereof
By using bisphenol A type epoxy resin, silica hollow microbead grafting carbon fiber and other components in the absorbing materials, and using vacuum high-speed shear and vulcanization processes, the magnetic permeability of existing high-temperature absorbing materials is solved. The problem of low performance has achieved the improvement of high magnetic permeability and high temperature resistance, and is suitable for anti-interference and identification applications in high-temperature environments.
Patent Information
- Application Number
- CN202411183475.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-27
- Publication Date
- 2024-12-13
AI Technical Summary
The existing high-temperature wave-resistant absorbent materials have low magnetic permeability and high frequency of use, making it difficult to maintain stability in high-temperature environments, and cannot fully exert anti-interference and recognition effects.
Using bisphenol A type epoxy resin, silica hollow microbead grafted carbon fiber, conductive carbon black, silicon carbide, barium titanate and carbon nanotubes, high magnetic conductivity is formed through vacuum high-speed shearing and vulcanization processes. The absorbing material with a high temperature resistance ensures the uniform distribution of fillers and the stability of the thermal conductivity network.
It significantly improves the magnetic permeability and high temperature resistance of wave absorbing materials, expands its application range, and maintains good thermal conductivity and wave absorption effects in high-temperature environments.
Smart Images

Figure BDA0005012879310000071 
Figure BDA0005012879310000081
Abstract
Description
Technical Field
[0001] The present application relates to a wave absorbing material, and more specifically, to a high temperature resistant ultra-high magnetic permeability wave absorbing material and a preparation method thereof. Background Art
[0002] Absorbing materials are mostly found in electrical components such as electronic equipment, absorbing and shielding near-frequency and near-level interference problems. High-temperature environments place higher requirements on the stability of absorbing materials.
[0003] The existing high temperature resistant absorbing material matrix, such as silicone resin, silicone rubber, etc., has a low magnetic permeability of absorbing materials prepared by calendering process, with the highest being only about 50, and such absorbing materials are used frequently. How to give the material better temperature resistance, expand the scope of use of the material, better apply it in some special high temperature resistant fields, give full play to the anti-interference effect, and accurately identify the effect, is a problem to be solved. Summary of the invention
[0004] In order to solve the problem that the absorbing material has both high magnetic permeability and high temperature resistance, the present application provides a high temperature resistant ultra-high magnetic permeability absorbing material and a preparation method thereof.
[0005] In the first aspect, the present application provides a high temperature resistant ultra-high magnetic permeability absorbing material, including agent A, agent B and base cloth, wherein agent A includes the following raw materials in parts by mass: 70-75 parts of bisphenol A epoxy resin, 15-20 parts of hollow silica microbeads grafted carbon fibers, 15-20 parts of conductive carbon black, 5-10 parts of silicon carbide, 5-10 parts of barium titanate, and 5-10 parts of carbon nanotubes; agent B includes the following raw materials in parts by mass: 30-35 parts of polyamide curing agent and 8-15 parts of acetone.
[0006] By adopting the above scheme, hollow silica microspheres are grafted onto carbon fibers, and hollow silica microspheres have air cavities, while the dielectric constant of air is close to 1, and the loss tangent is close to 0. By adding hollow silica microspheres, the obtained wave-absorbing material has good wave transmittance, and carbon fibers, conductive carbon black, silicon carbide, barium titanate, and carbon nanotubes have good thermal conductivity and magnetic permeability. The present application improves the wave-absorbing effect by combining the absorption and scattering of conductive carbon black in the matrix, the excellent interface polarization of silicon carbide, the excellent dielectric properties of carbon nanotubes and barium titanate, etc., but by The added mass of fillers in the absorbing material is limited, and a good thermal conductive network cannot be formed. The present application avoids the situation in which only point contact and poor thermal conductivity occur between the carbon fiber and other fillers during the overlapping process by grafting hollow silica microbeads onto carbon fibers. The prepared hollow silica microbead grafted carbon fibers have a lower density, so that they can exist more evenly and stably in the matrix of the present application. At the same time, the structural load level of the carbon fiber surface is increased, and a certain steric hindrance is formed with other fillers. The carbon fibers are not easily deformed under high temperature conditions, and the thermal conductive path is more stable.
[0007] In a specific embodiment, the preparation steps of silica hollow microspheres grafted carbon fibers include: mixing a silane coupling agent, ethanol, and water, stirring evenly to obtain a mixed solution, adding carbon fibers and stirring, filtering, and drying to obtain silane-modified carbon fibers, adding silane-modified carbon fibers and silica hollow microspheres to ethyl acetate, stirring, filtering, washing, and drying to obtain silica hollow microspheres grafted carbon fibers.
[0008] By adopting the above scheme, the preparation method is simple, the effect of grafting the hollow silica microbeads with the carbon fiber is good, it is not easy to break in the subsequent preparation process, and the hollow silica microbeads can be more evenly distributed on the surface of the carbon fiber.
[0009] In a specific embodiment, the particle size of the hollow silica microbeads is 800-900 nm.
[0010] By adopting the above scheme, the particle size of the hollow silica microbeads is appropriate, which is not too large to cause good grafting and coating, nor too small to cause failure to form a good thermal conductive network between fibers.
[0011] In a specific embodiment, the preparation step of agent A includes vacuum high-speed shearing.
[0012] By adopting the above scheme, after vacuum high-speed shearing, the filler in the prepared agent A forms a better orientation, the carbon fiber and the other long strip-shaped fillers are arranged relatively straight, and the heat can be conducted out faster in the orientation. Silica hollow microbeads are grafted between the carbon fiber segments. The silica hollow microbeads are evenly arranged to form a heat insulation layer as the relatively flat carbon fiber moves after shearing. The oriented carbon fiber drives other fillers to be oriented and quickly conducts heat in the orientation direction. Therefore, the absorbing material of the present application can protect the absorbing material from both heat insulation and heat conduction aspects by adding silica hollow microbeads grafted carbon fiber under the components of the present application and performing vacuum high-speed shearing, and the shearing process does not introduce bubbles. The filler in the obtained absorbing material has a large density, and the absorbing effect and high temperature resistance effect are good.
[0013] In a specific embodiment, the shear line speed is 40-45 m / s.
[0014] By adopting the above scheme, the shearing of agent A is better, wherein various absorbing fillers are oriented and connected, and at the same time, the shearing speed will not be too fast to destroy the structure of the hollow silica microbeads grafted carbon fiber.
[0015] In a specific embodiment, the carbon nanotubes are carbon nanotubes modified by an epoxy silane coupling agent.
[0016] By adopting the above scheme, the carbon nanotubes modified by the epoxy silane coupling agent have better compatibility in the material, better fluidity during the shearing process, and can be more evenly connected in the oriented carbon fibers, so that the obtained absorbing material has better orientation and heat conduction effects.
[0017] In a specific embodiment, the preparation steps of epoxysilane coupling agent modified carbon nanotubes include: adding nano-alumina and epoxysilane coupling agent into toluene for ultrasonic dispersion, reaction, and then filtering and drying to obtain epoxysilane coupling agent modified carbon nanotubes.
[0018] By adopting the above scheme, the preparation steps of carbon nanotubes modified with epoxy silane coupling agent are relatively simple, the yield of carbon nanotubes modified with epoxy silane coupling agent is high, and the modification effect is relatively stable.
[0019] In a specific embodiment, the mass ratio of the hollow silica microbeads grafted carbon fibers to the epoxy silane coupling agent modified carbon nanotubes is: (1-3):1.
[0020] Preferably, the mass ratio of hollow silica microbeads grafted carbon fibers to epoxy silane coupling agent modified carbon nanotubes is: (1.2-1.8):1.
[0021] The preferred mass ratio of hollow silica microbeads grafted carbon fibers to epoxy silane coupling agent modified carbon nanotubes is 1.6:1.
[0022] By adopting the above scheme, the structure of the heat conduction flux and the wave absorbing network is better.
[0023] In a second aspect, the present application provides a method for preparing a high temperature resistant ultra-high magnetic permeability absorbing material, the preparation method comprising the following steps: S1. Weigh and mix agent A and agent B respectively according to the mass ratio, then add agent B to agent A twice, stir evenly, vacuum high-speed shear, and evacuate to obtain a mixture; S2. Coat the mixture evenly on the base fabric, then heat it at 50-70℃ for 0.5-1.5h, dry it, and then vulcanize it to obtain the absorbing material.
[0024] By adopting the above scheme, the preparation method is relatively simple, and the prepared absorbing material is relatively uniform and stable, and is tightly connected to the base fabric.
[0025] In a specific implementation scheme, the vulcanization is placed in a flat vulcanizer, kept at 60-80°C, 1-2MPa for 2-3 hours, kept at 150-160°C, 1-2MPa for 2-3 hours, and then cooled and depressurized. By adopting the above scheme, the obtained absorbing material is more uniform and stable, with uniform stress and fewer defects.
[0026] In summary, this application has the following beneficial effects: The present application combines the components in the formula and limits them to a certain mass ratio, so that the prepared absorbing material has better heat resistance, expands the use scope of the material, and is better applied in some special high-temperature resistant fields. By adding a certain mass of hollow silica microbeads to graft carbon fibers and performing vacuum high-speed shearing, the hollow silica microbeads are oriented and connected in the absorbing material as the carbon fibers flow, and the oriented carbon fibers drive other fillers to be oriented, while improving the heat resistance of the absorbing material from the two aspects of heat insulation and heat conduction. By adding a certain mass of epoxy silane coupling agent to modify carbon nanotubes, their compatibility and fluidity in the material are improved, and the flow during the shearing process forms a better and more uniform heat conduction and absorbing network. DETAILED DESCRIPTION
[0027] The hollow silica microspheres in this application were purchased from Xi'an Qiyue Biotechnology Co., Ltd. (800-900 nm). The experimental reagents in the preparation examples, embodiments, and comparative examples, unless otherwise specified, are conventional commercial brands or obtained through conventional preparation processes.
[0028] Preparation Example Preparation Example 1: Silicon dioxide hollow microspheres grafted onto carbon fibers: 50g of silane coupling agent KH-540, 300ml of ethanol and 60g of pure water were mixed and stirred to obtain a mixed solution; 100g of carbon fiber was added to the mixed solution, stirred at room temperature for 1 hour, filtered and dried to obtain silane-modified carbon fiber; silane-modified glass fiber and 20g of hollow silica microspheres were added to 300ml of ethyl acetate, stirred for 4 hours, filtered, washed and dried to obtain hollow silica microsphere grafted carbon fiber Preparation Example 2: Carbon Nanotubes Modified by Epoxysilane Coupling Agent 50 g of carbon nanotubes and 15 g of epoxysilane coupling agent KH-172 were added to 1000 ml of toluene, and then ultrasonically dispersed at a power of 300 W for 30 minutes, reacted at 90° C., filtered, and dried to obtain epoxysilane coupling agent-modified nano-alumina.
[0029] Preparation Example 3: Aminosilane Coupling Agent Modified Carbon Nanotubes 50 g of silane coupling agent KH-540, 300 ml of ethanol and 60 g of pure water were mixed and stirred evenly to obtain a mixed solution; 100 g of carbon nanotubes were added to the mixed solution, stirred at room temperature for 1 hour, filtered and dried to obtain silane-modified carbon nanotubes. Example
[0030] Example 1 In this embodiment, agent A includes the following raw materials in parts by mass: 700 g of bisphenol A epoxy resin, 150 g of hollow silica microspheres grafted carbon fibers obtained in Preparation Example 1, 150 g of conductive carbon black, 50 g of silicon carbide, 50 g of barium titanate, and 100 g of carbon nanotubes; agent B includes the following raw materials in parts by mass: 300 g of polyamide curing agent and 150 g of acetone.
[0031] S1. Weigh and mix Agent A according to the mass ratio, and then perform vacuum high-speed shearing at a linear speed of 45 m / s to obtain Agent A. Weigh and mix Agent B according to the mass ratio, and then add Agent B to Agent A twice, stir evenly, and evacuate to obtain a mixture; S2. Evenly coat the mixture on a nylon cloth, and then heat it at 50°C for 1 hour, dry it, and then place it in a flat vulcanizer, keep it warm at 75°C and 1 for 2 hours, and then keep it warm at 150°C and 2MPa for 2 hours, and then reduce the temperature and pressure to obtain an absorbing material.
[0032] Example 2 In this embodiment, agent A includes the following raw materials in parts by mass: 750 g of bisphenol A epoxy resin, 200 g of hollow silica microspheres grafted carbon fiber obtained in Preparation Example 1, 150 g of conductive carbon black, 50 g of silicon carbide, 50 g of barium titanate, and 100 g of carbon nanotubes; agent B includes the following raw materials in parts by mass: 300 g of polyamide curing agent and 80 g of acetone.
[0033] S1. Weigh and mix Agent A according to the mass ratio, and then perform vacuum high-speed shearing at a linear speed of 45 m / s to obtain Agent A. Weigh and mix Agent B according to the mass ratio, and then add Agent B to Agent A twice, stir evenly, and evacuate to obtain a mixture; S2. Evenly coat the mixture on a nylon cloth, and then heat it at 50°C for 1 hour, dry it, and then place it in a flat vulcanizer, keep it warm at 75°C and 1 for 2 hours, and then keep it warm at 150°C and 2MPa for 2 hours, and then reduce the temperature and pressure to obtain an absorbing material.
[0034] Example 3 In this embodiment, agent A includes the following raw materials in parts by mass: 700 g of bisphenol A epoxy resin, 150 g of hollow silica microspheres grafted carbon fiber obtained in Preparation Example 1, 200 g of conductive carbon black, 100 g of silicon carbide, 100 g of barium titanate, and 50 g of carbon nanotubes; agent B includes the following raw materials in parts by mass: 300 g of polyamide curing agent and 150 g of acetone.
[0035] S1. Weigh and mix Agent A according to the mass ratio, and then perform vacuum high-speed shearing at a linear speed of 45 m / s to obtain Agent A. Weigh and mix Agent B according to the mass ratio, and then add Agent B to Agent A twice, stir evenly, and evacuate to obtain a mixture; S2. Evenly coat the mixture on a nylon cloth, and then heat it at 50°C for 1 hour, dry it, and then place it in a flat vulcanizer, keep it warm at 75°C and 1 for 2 hours, and then keep it warm at 150°C and 2MPa for 2 hours, and then reduce the temperature and pressure to obtain an absorbing material.
[0036] Example 4 In this embodiment, agent A includes the following raw materials in parts by mass: 700 g of bisphenol A epoxy resin, 150 g of hollow silica microspheres grafted carbon fibers prepared in Preparation Example 1, 150 g of conductive carbon black, 50 g of silicon carbide, 50 g of barium titanate, and 100 g of carbon nanotubes modified with an epoxy silane coupling agent prepared in Preparation Example 2; and agent B includes the following raw materials in parts by mass: 300 g of a polyamide curing agent and 150 g of acetone.
[0037] S1. Weigh and mix Agent A according to the mass ratio, and then perform vacuum high-speed shearing at a linear speed of 45 m / s to obtain Agent A. Weigh and mix Agent B according to the mass ratio, and then add Agent B to Agent A twice, stir evenly, and evacuate to obtain a mixture; S2. Evenly coat the mixture on a nylon cloth, and then heat it at 50°C for 1 hour, dry it, and then place it in a flat vulcanizer, keep it warm at 75°C and 1 for 2 hours, and then keep it warm at 150°C and 2MPa for 2 hours, and then reduce the temperature and pressure to obtain an absorbing material.
[0038] Example 5 In this embodiment, agent A includes the following raw materials in parts by mass: 700 g of bisphenol A epoxy resin, 150 g of hollow silica microspheres grafted carbon fibers prepared in Preparation Example 1, 150 g of conductive carbon black, 50 g of silicon carbide, 50 g of barium titanate, and 100 g of aminosilane coupling agent-modified carbon nanotubes prepared in Preparation Example 3; agent B includes the following raw materials in parts by mass: 300 g of polyamide curing agent and 150 g of acetone.
[0039] S1. Weigh and mix Agent A according to the mass ratio, and then perform vacuum high-speed shearing at a linear speed of 45 m / s to obtain Agent A. Weigh and mix Agent B according to the mass ratio, and then add Agent B to Agent A twice, stir evenly, and evacuate to obtain a mixture; S2. Evenly coat the mixture on a nylon cloth, and then heat it at 50°C for 1 hour, dry it, and then place it in a flat vulcanizer, keep it warm at 75°C and 1 for 2 hours, and then keep it warm at 150°C and 2MPa for 2 hours, and then reduce the temperature and pressure to obtain an absorbing material.
[0040] Example 6 In this embodiment, agent A includes the following raw materials in parts by mass: 700 g of bisphenol A epoxy resin, 125 g of hollow silica microspheres grafted carbon fibers prepared in Preparation Example 1, 150 g of conductive carbon black, 50 g of silicon carbide, 50 g of barium titanate, and 125 g of carbon nanotubes modified with an epoxy silane coupling agent prepared in Preparation Example 2; and agent B includes the following raw materials in parts by mass: 300 g of a polyamide curing agent and 150 g of acetone.
[0041] S1. Weigh and mix Agent A according to the mass ratio, and then perform vacuum high-speed shearing at a linear speed of 45 m / s to obtain Agent A. Weigh and mix Agent B according to the mass ratio, and then add Agent B to Agent A twice, stir evenly, and evacuate to obtain a mixture; S2. Evenly coat the mixture on a nylon cloth, and then heat it at 50°C for 1 hour, dry it, and then place it in a flat vulcanizer, keep it warm at 75°C and 1 for 2 hours, and then keep it warm at 150°C and 2MPa for 2 hours, and then reduce the temperature and pressure to obtain an absorbing material.
[0042] Example 7 In this embodiment, agent A includes the following raw materials in parts by mass: 700 g of bisphenol A epoxy resin, 187.5 g of hollow silica microspheres grafted carbon fibers prepared in Preparation Example 1, 150 g of conductive carbon black, 50 g of silicon carbide, 50 g of barium titanate, and 62.5 g of carbon nanotubes modified with an epoxy silane coupling agent prepared in Preparation Example 2; and agent B includes the following raw materials in parts by mass: 300 g of a polyamide curing agent and 150 g of acetone.
[0043] S1. Weigh and mix Agent A according to the mass ratio, and then perform vacuum high-speed shearing at a linear speed of 45 m / s to obtain Agent A. Weigh and mix Agent B according to the mass ratio, and then add Agent B to Agent A twice, stir evenly, and evacuate to obtain a mixture; S2. Evenly coat the mixture on a nylon cloth, and then heat it at 50°C for 1 hour, dry it, and then place it in a flat vulcanizer, keep it warm at 75°C and 1 for 2 hours, and then keep it warm at 150°C and 2MPa for 2 hours, and then reduce the temperature and pressure to obtain an absorbing material.
[0044] Example 8 In this embodiment, agent A includes the following raw materials in parts by mass: 700 g of bisphenol A epoxy resin, 153.8 g of hollow silica microspheres grafted carbon fibers prepared in Preparation Example 1, 150 g of conductive carbon black, 50 g of silicon carbide, 50 g of barium titanate, and 96.1 g of carbon nanotubes modified with epoxy silane coupling agent prepared in Preparation Example 2; agent B includes the following raw materials in parts by mass: 300 g of polyamide curing agent and 150 g of acetone.
[0045] S1. Weigh and mix Agent A according to the mass ratio, and then perform vacuum high-speed shearing at a linear speed of 45 m / s to obtain Agent A. Weigh and mix Agent B according to the mass ratio, and then add Agent B to Agent A twice, stir evenly, and evacuate to obtain a mixture; S2. Evenly coat the mixture on a nylon cloth, and then heat it at 50°C for 1 hour, dry it, and then place it in a flat vulcanizer, keep it warm at 75°C and 1 for 2 hours, and then keep it warm at 150°C and 2MPa for 2 hours, and then reduce the temperature and pressure to obtain an absorbing material.
[0046] Example 9 In this embodiment, agent A includes the following raw materials in parts by mass: 700 g of bisphenol A epoxy resin, 200 g of hollow silica microspheres grafted carbon fibers prepared in Preparation Example 1, 150 g of conductive carbon black, 50 g of silicon carbide, 50 g of barium titanate, and 50 g of carbon nanotubes modified with an epoxy silane coupling agent prepared in Preparation Example 2; and agent B includes the following raw materials in parts by mass: 300 g of a polyamide curing agent and 150 g of acetone.
[0047] S1. Weigh and mix Agent A according to the mass ratio, and then perform vacuum high-speed shearing at a linear speed of 45 m / s to obtain Agent A. Weigh and mix Agent B according to the mass ratio, and then add Agent B to Agent A twice, stir evenly, and evacuate to obtain a mixture; S2. Evenly coat the mixture on a nylon cloth, and then heat it at 50°C for 1 hour, dry it, and then place it in a flat vulcanizer, keep it warm at 75°C and 1 for 2 hours, and then keep it warm at 150°C and 2MPa for 2 hours, and then reduce the temperature and pressure to obtain an absorbing material.
[0048] Example 10 In this embodiment, agent A includes the following raw materials in parts by mass: 700 g of bisphenol A epoxy resin, 150 g of hollow silica microspheres grafted carbon fibers obtained in Preparation Example 1, 150 g of conductive carbon black, 50 g of silicon carbide, 50 g of barium titanate, and 100 g of carbon nanotubes; agent B includes the following raw materials in parts by mass: 300 g of polyamide curing agent and 150 g of acetone.
[0049] S1. Weigh and mix Agent A according to the mass ratio, and then vacuum high-speed shear at a linear speed of 45 m / s to obtain Agent A; weigh and mix Agent B according to the mass ratio, and then add Agent B to Agent A twice, stir evenly, and vacuum to obtain a mixture; S2. Coat the mixture evenly on a nylon cloth, and then heat it at 50°C for 1h, dry it, and then place it in a flat vulcanizer, keep it warm at 150°C and 2MPa for 2h, and then reduce the temperature and pressure to obtain an absorbing material.
[0050] Comparative Example Comparative Example 1 In this embodiment, agent A includes the following raw materials in parts by mass: 700 g of bisphenol A epoxy resin, 75 g of hollow silica microspheres, 75 g of carbon fiber, 150 g of conductive carbon black, 50 g of silicon carbide, 50 g of barium titanate, and 100 g of carbon nanotubes; and agent B includes the following raw materials in parts by mass: 300 g of polyamide curing agent and 150 g of acetone.
[0051] S1. Weigh and mix Agent A according to the mass ratio, and then perform vacuum high-speed shearing at a linear speed of 45 m / s to obtain Agent A. Weigh and mix Agent B according to the mass ratio, and then add Agent B to Agent A twice, stir evenly, and evacuate to obtain a mixture; S2. Evenly coat the mixture on a nylon cloth, and then heat it at 50°C for 1 hour, dry it, and then place it in a flat vulcanizer, keep it warm at 75°C and 1 for 2 hours, and then keep it warm at 150°C and 2MPa for 2 hours, and then reduce the temperature and pressure to obtain an absorbing material.
[0052] Example 2 In this embodiment, agent A includes the following raw materials in parts by mass: 800 g of bisphenol A epoxy resin, 150 g of hollow silica microspheres grafted carbon fibers obtained in Preparation Example 1, 150 g of conductive carbon black, 50 g of silicon carbide, 50 g of barium titanate, and 100 g of carbon nanotubes; agent B includes the following raw materials in parts by mass: 300 g of polyamide curing agent and 180 g of acetone.
[0053] S1. Weigh and mix Agent A according to the mass ratio, and then perform vacuum high-speed shearing at a linear speed of 45 m / s to obtain Agent A. Weigh and mix Agent B according to the mass ratio, and then add Agent B to Agent A twice, stir evenly, and evacuate to obtain a mixture; S2. Evenly coat the mixture on a nylon cloth, and then heat it at 50°C for 1 hour, dry it, and then place it in a flat vulcanizer, keep it warm at 75°C and 1 for 2 hours, and then keep it warm at 150°C and 2MPa for 2 hours, and then reduce the temperature and pressure to obtain an absorbing material.
[0054] Performance test test 1: Detect the magnetic permeability μ1 of the absorbing materials prepared in the embodiment and the comparative example, and the test results are summarized in Table 1; Test 2: The absorbing materials prepared in the embodiments and comparative examples were placed at 270°C for 30s, and the magnetic permeability μ2 was tested. The magnetic permeability retention rate / % was calculated according to μ1 / μ2×100%. The test results are summarized in Table 1.
[0055] Table 1 This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A high temperature resistant ultra-high magnetic permeability absorbing material, Features: The wave absorbing material comprises an agent A, an agent B and a base fabric. The agent A comprises the following raw materials in parts by mass: 70-75 parts of bisphenol A epoxy resin, 15-20 parts of hollow silica microbeads grafted carbon fibers, 15-20 parts of conductive carbon black, 5-10 parts of silicon carbide, 5-10 parts of barium titanate and 5-10 parts of carbon nanotubes. The agent B comprises the following raw materials in parts by mass: 30-35 parts of a polyamide curing agent and 8-15 parts of acetone.
2. A high temperature resistant ultra-high magnetic permeability absorbing material according to claim 1, Features: The preparation steps of the hollow silica microspheres grafted carbon fibers include: mixing a silane coupling agent, ethanol and water, stirring evenly to obtain a mixed solution, adding carbon fibers and stirring, filtering, and drying to obtain silane-modified carbon fibers, and adding the silane-modified carbon fibers and hollow silica microspheres to ethyl acetate, stirring, filtering, washing, and drying to obtain hollow silica microspheres grafted carbon fibers.
3. The high temperature resistant ultra-high magnetic permeability absorbing material according to claim 1, Features: The particle size of the hollow silicon dioxide microspheres is 800-900 nm.
4. The high temperature resistant ultra-high magnetic permeability absorbing material according to claim 1, Features: The preparation step of the agent A includes vacuum high-speed shearing.
5. A high temperature resistant ultra-high magnetic permeability absorbing material according to claim 4, Features: The shearing line speed is 40-45 m / s.
6. The high temperature resistant ultra-high magnetic permeability absorbing material according to claim 1, Features: The carbon nanotubes are carbon nanotubes modified by epoxy silane coupling agents.
7. A high temperature resistant ultra-high magnetic permeability absorbing material according to claim 6, Features: The preparation steps of the epoxy silane coupling agent modified carbon nanotubes include: adding nano-alumina and epoxy silane coupling agent into toluene for ultrasonic dispersion, reaction, then suction filtration and drying to obtain epoxy silane coupling agent modified carbon nanotubes.
8. The high temperature resistant ultra-high magnetic permeability absorbing material according to claim 6, Features: The mass ratio of the hollow silica microbeads grafted carbon fibers to the epoxy silane coupling agent modified carbon nanotubes is: (1-3):
1.
9. A method for preparing a high temperature resistant ultra-high magnetic permeability absorbing material according to any one of claims 1 to 8, Features: The preparation method comprises the following steps: S1. Weigh and mix agent A and agent B respectively according to the mass ratio, then add agent B to agent A twice, stir evenly, vacuum high-speed shear, and evacuate to obtain a mixture; S2. Coat the mixture evenly on the base fabric, then heat it at 50-70℃ for 0.5-1.5h, dry it, and then vulcanize it to obtain the absorbing material.
10. The method for preparing a high temperature resistant ultra-high magnetic permeability absorbing material according to claim 9, Features: The vulcanization is carried out in a flat vulcanizing machine, keeping the temperature at 60-80° C. and 1-2 MPa for 2-3 hours, keeping the temperature at 150-160° C. and 1-2 MPa for 2-3 hours, and then reducing the temperature and pressure.
